ChemInform Abstract: Mizoroki—Heck Reactions Catalyzed by Palladium Dichloro‐bis(aminophosphine) Complexes under Mild Reaction Conditions. The Importance of Ligand Composition on the Catalytic Activity. Issue 40 (12th September 2013) - Oberholzer, Miriam; Frech, Christian M.
Abstract An air stable palladium complex comprising two tripiperidinophosphine ligands is easily prepared and successfully applied as a catalyst for the Mizoroki—Heck reaction of aryl bromides with different alkenes [46 examples].